2023
DOI: 10.7554/elife.82232
|View full text |Cite
|
Sign up to set email alerts
|

Loss of aquaporin-4 results in glymphatic system dysfunction via brain-wide interstitial fluid stagnation

Abstract: The glymphatic system is a fluid transport network of cerebrospinal fluid (CSF) entering the brain along arterial perivascular spaces, exchanging with interstitial fluid (ISF), ultimately establishing directional clearance of interstitial solutes. CSF transport is facilitated by the expression of aquaporin-4 (AQP4) water channels on the perivascular endfeet of astrocytes. Mice with genetic deletion of AQP4 (AQP4 KO) exhibit abnormalities in the brain structure and molecular water transport. Yet, no studies hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 115 publications
4
52
0
Order By: Relevance
“…These brain regions exhibited the highest AQP4 expression in WT mice (Gomolka et al, 2023) which supports the notion that the drug is inhibiting AQP4, as areas with the most AQP4 were most affected by drug treatment. Our findings further validate that slow MR diffusion is a surrogate indicator of glymphatic function (Gomolka et al, 2023), and support the observation that AER-271 reduces glymphatic flow. Here we find the inhibitor reduced transmembrane water exchange leading to inhibition of ISF volume increases in WT mice, as measured using ADC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These brain regions exhibited the highest AQP4 expression in WT mice (Gomolka et al, 2023) which supports the notion that the drug is inhibiting AQP4, as areas with the most AQP4 were most affected by drug treatment. Our findings further validate that slow MR diffusion is a surrogate indicator of glymphatic function (Gomolka et al, 2023), and support the observation that AER-271 reduces glymphatic flow. Here we find the inhibitor reduced transmembrane water exchange leading to inhibition of ISF volume increases in WT mice, as measured using ADC.…”
Section: Discussionsupporting
confidence: 76%
“…The motion-correction was performed four times or until no further improvement in reference to the first image acquired using the first bvalue (b0), with visual inspection to confirm correctness. To assess the water molecules mobility within the brain parenchyma in the motioncorrected DWI images from each diffusion-encoding direction, we performed evaluation as presented previously (Gomolka et al, 2023).…”
Section: Dwi Processing and Analysismentioning
confidence: 99%
“…The polarized distribution of AQP4 in the brain is important for regulating water transport in both normal and pathological conditions (Kitchen et al, 2020; Manley et al, 2004; Nakada, 2014), with evidence indicating that vascular polarized AQP4 expression is more important for effective fluid transport, rather than total AQP4 levels in the tissue (Gomolka et al, 2023; Hablitz et al, 2020; Mestre et al, 2018; Sylvain et al, 2021). It is also noteworthy that the effect of (S)‐roscovitine took place in the cortex but did not impact the striatum where AQP4 is more diffusely expressed in astrocyte processes, suggesting that AQP4 expression is regulated in a region‐specific manner which may be related to the functional differences of astrocytes in different brain regions (Aoyama et al, 2012; Guo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of AQP4 in the glymphatic system has been confirmed in multiple lines of AQP4 KO mice, as well as pharmacological blockade by the AQP4 inhibitor, TGN-020 [ 38 , 39 ]. It has recently been shown that AQP4 KO mice display an enlarged interstitial volume and decreased CSF volume without an altered CSF production rate [ 40 ]. The stagnation of ISF and enlargement of the ISF space might be a consequence of an overall reduction in glymphatic transport.…”
Section: Glymphatic Clearance and Its Implications In Admentioning
confidence: 99%